Halal food consumption as perceived by the non-Muslim in Malaysia - Yunos, Nasruddin; Mohamad, Zulkifli; Ghazali, Mohd Alikhsan; Awang, Mohd Daud (Malaysian Consumer and Family Economics Association, 2018)
Halal food is the food handled according to the Sharia law and the food is subjected by the approved certification systems which provide guarantee to consumers that the food is free from any forbidden components guided by the Islamic law. The halal food is suitable not for only Muslims, but also for the non-Muslims. The outcomes of this study based on interviews were presented with reviewed literatures to answer three questions which were regarding on the non-Muslim’s understandings about the concept of halal, the contributing factors towards halal food consumption among non-Muslim, and confusions related to halal food. The study found that despite the lack of understanding about the concept of halal, the non-Muslim accepted halal food as a part of their food choices. Furthermore, the lack of information and confusion about the halal label were identified as main area of confusions related to halal food. This finding helps to enhance an understanding among the diverse ethnicities in Malaysia, and to generate revenues and enhance marketability of halal food explicitly.